Democracy, income inequality and economic growth nexus: The case of Pakistan - Rafi Amir-ud-Din; Rana Ejaz Ali Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
Democracy, income inequality and economic development are considered to be interlinked with one another in a complex way. The weak growth of political institutions and uncertainty about the continuity of democratic regimes in Pakistan has important consequences for the economic growth and level of income inequality. We analyzed the interaction among democracy, income inequality and economic growth during 1963-2016 using 3SLS and alternative estimation methods. Our findings suggest that democracy, income inequality and economic development are endogenously interlinked in Pakistan. The significance of this study lies in the fact that it highlights the intrinsic value of the political institutions and their benign role in promoting economic growth and reducing inequality. The level of inequality affects the economic growth negatively but conversely economic growth rate does not have a significant impact on inequality thus rejecting the trickle down hypothesis. Inequality is also found to have a significant negative impact on the democracy. Democracy and public expenditures on community, social and public services also reduce inequality.
Keywords: 330; democracy; income inequality; economic growth; political rights; political institutions; fiscal policy